Extensive Necrotic Purpura in Levamisole‐Adulterated Cocaine Abuse – A Case Report. Issue 6 (8th August 2016) - Le Garff, Erwan; Tournel, Gilles; Becquart, Coralie; Cottencin, Olivier; Dupin, Nicolas; Delaporte, Emmanuel; Hedouin, Valéry
Abstract: Levamisole, which is used as an adulterated compound of cocaine, is currently being seen year after year in cocaine intoxication. For a few cases in the last decade, necrotic purpura and neutropenia after levamisole/cocaine intoxication have been described in the medical community. Herein, we present an original case of levamisole intoxication of a 40‐year‐old woman who smoked heroin and cocaine few during a month. She rapidly presented an extensive necrotic purpura of the nose, cheeks and extremities (lower and upper), and immunologic reactions (positive anti‐MPO and anti‐HNE). Levamisole was detected on hairs with ultra‐high performance liquid chromatography and tandem mass spectrometry. The case reports also a probable cocaine supplier deceit, which bring pure drug for hospital investigation after the intoxication of his client. The intoxicated woman had survived with several skin and chronic pain complications. That case recalls the knowledge about levamisole with a short review of the forensic literature.